Ultrahigh-quality electromagnetically induced absorption resonances in a cesium vapor cell. (4th October 2019) - Brazhnikov, D V; Ignatovich, S M; Novokreshchenov, A S; Skvortsov, M N
Abstract: Electromagnetically induced absorption (EIA) of cesium atoms exposed to counter-propagating light waves with orthogonal linear polarizations is studied. Probe beam transmission through a buffer gas-filled vapor cell is monitored as a function of a static magnetic field applied parallel to the wave vectors. The light waves are tuned to a single dipole transition F g → F e in the D1 line ( λ = 894.6 nm). The proposed magneto-optical configuration helps overcome a long-standing problem in obtaining high-contrast EIA resonances in conjunction with narrow linewidths. Our experiments demonstrate EIA contrast with respect to a broad Doppler absorption background ( C D ) as high as 1630%. Thus, a high value of C D means that background absorption is almost absent, and the vapor cell transmission profile represents only a single narrow resonance. This result is unique for EIA as well as for electromagnetically induced transparency (EIT) effects, because usually in a resonant medium, narrow EIT or EIA resonances are accompanied by natural-linewidth or other broad spectral features, even in the case of cold atoms. The resonance contrast with respect to the light transmission background ( C back ) is also high enough, reaching 75% in the experiments. The full width at half maximum of the narrowest observed EIA is approximately 0.77 mG (0.7 × 0.77 = 540 Hz in the frequency domain). The considered simple scheme has good prospects for the development of various quantum magneto-optical devices such as optical switches and atomic magnetometers.